PLACE OR NON-PLACE: A COMPARATIVE APPRAISAL ON PLACE THEORIES - Uzunkaya, Asli; Kerestecioglu, Funda; Koca, Senem Kaymaz (STEF92 TECHNOLOGY LTD, 2014)
Along with modernism 'space', one of the main interests of architecture, started to be handled as an empty, abstract and measurable notion. This approach also brought about many criticisms that mainly centered on the issues such as loss of meaning in space, dedifferentiation of space and estrangement from people-oriented space design. At the same time a series of studies which aimed to re-fill in space -with meaning- introduced architectural literature with a new notion: 'Place'. 'Place', which was put forward against the abstract 'space' of modernism, was opened up for discussion in a broad scope which tried to re-explore of relationship between space and its environment, re-product of context and re-relate space with the concepts of belonging, meaning and experience. In this respect, this research focuses to examine the change which this discussion has undergone until today; and methodologically divides place theories in two main chapters: 'Defences/Arguments of Notion of Place' and 'Critical Thinkings on Notion of Place'. 'Defences/Arguments of Notion of Place' are organised in three sub-chapters each of which has examined place from different point of views. These sub-chapters are named as 'Place Against the Abstract Space, and Phenomenological Approach', 'Context and Structualism' and 'Regionalism and Critical Regionalism'. On the other hand, 'Critical Thinkings on Notion of Place', which has focused on reproducing notion of place -while transforming it-, are examined in four sub-chapters. These are named as 'Non-Place', 'Disengagement from Context, and Post-Structualism', 'Becoming Architecture, and Deterritorialization' and 'Social Place'. The appraisal of 'place' that has been carried out by being organised within this methodological scope along the research is schematised in the conclusion part of the research. It should be noted that the research produces a sequence of notions that are open to comparison/interpretation through the schemes. Moreover, through such an appraisal on place theories raising awareness on relationship between architecture and place and generating a basis for comparison/interpretation of place theories are the main purposes of this research.
Keywords: Modernism; space; place; context; non-place; Arts & Humanities - Other Topics